Controlling corporate sickness : lessons from experiences for man agers and bankers - Gupta, Lakshmi Chandra, 1930-; Sekhar, Archana (Delhi ; New York : Oxford University Press, New York, 1988)
With reference to India.
Includes index.
Includes Bibliographical References (p. [107]-108).
Keywords: Corporate turnarounds -- Management